Design and fabrication of an engineered multi-mode worker toolkit for construction and agriculture industries - Imran Khan; Hazrat Ali; Maaz Ahmed; Muhammad Abas; Muhammad Zeeshan Zahir; Muhammad Asif; Fatima Hira; Abdullah Khalil (Mehran University Research Journal of Engineering and Technology)
The workers at construction and agricultural sites face many problems regarding load carrying (body pains), which results in less work efficiency. Therefore, the idea of designing a toolkit is put forward, with the help of which the workers could do their work easily and efficiently. This study aims to design and fabricate a low-cost toolkit that is lighter and easily accessible to all workers. The toolkit is designed to be used in different positions or modes. The most important step in this project is material selection, as it will define the toolkit's final weight, cost, and strength. Various materials, such as wood, bamboo, aluminum, steel, etc., were compared based on their physical properties, such as their strength, weight, and behavior in changing weather. The material selected is steel due to its high strength, weldability, and low cost. A design was finalized by incorporating safety and worker comfort. An ANSYS analysis was then performed on the proposed design to check it for loading capacity and deformation in various modes of operation. After performing the ANSYS analysis, the toolkit was fabricated and tested at various modes of operation. It was found that the tool performed exceptionally well at loads less than 20 Kg, whereas there were some minute deflection errors (max. error of 1.7 mm) at loads greater than 35 Kg.